Association between end‐stage diabetic nephropathy and MTHFR (C677T and A1298C) gene polymorphisms. Issue 2 (29th January 2019) - Ramanathan, Gnanasambandan; Harichandana, Bollimpalli; Kannan, Suresh; Elumalai, Ramprasad; SFD, Paul
ABSTRACT: Aim: Methylenetetrahydrofolate reductase (MTHFR) is a regulatory enzyme of homocysteine metabolism. The C677T and A1298C polymorphism of the MTHFR gene has been reported to be associated with elevated plasma homocysteine in patients with Diabetic nephropathy. This study aimed to investigate the influence of the C677T and A1298C polymorphisms on the progression chronic kidney disease in diabetic nephropathy of south Indian population. Methods: We genotyped 145 DN cases and 100 controls for the C677T and A1298C polymorphisms using PCR‐RFLP based protocols, and all diabetic nephropathy cases divided into two groups based on CKD stages: 60 DN cases were early stage (CKD1 to CKD3) and 85 DN cases were advanced stage (CKD4 and CKD5). Association χ 2 and univariate analysis were performed. Results: The C677T (OR = 4.2; 95% CI = 2.31–7.64 and P =  0.001) and A1298C (OR = 2.8; 95% CI = 1.05–7.57 and P =  0.033) polymorphism was shown that the significant association between the cases and control. Furthermore, the MTHFR gene polymorphism C677T (OR = 2.48; 95% CI = 1.25–4.9 and P =  0.008) was observed that the significant contribution of the progression of CKD in DN. Conclusion: These findings suggest that the C677T and A1298C polymorphism of MTHFR gene was associated with diabetic nephropathy in a south Indian population. Furthermore, the present study provides evidence that the C677T polymorphism was associated with CKD progression in DN. Summary at a Glance: This manuscript adds to the body of work on methylenetetrahydrofolate reductase (MTHFR) gene polymorphisms and diabetic nephropathy in a different ethnic group.